The Protective Role of Group Identity: Sectarian Antisocial Behavior and Adolescent Emotion Problems. Issue 2 (17th May 2013) - Merrilees, Christine E.; Taylor, Laura K.; Goeke‐Morey, Marcie C.; Shirlow, Peter; Cummings, E. Mark; Cairns, Ed
<x xml:space="preserve">Abstract</x> The protective role of strength of group identity was examined for youth in a context of protracted political conflict. Participants included 814 adolescents (Mage = 13.61, SD = 1.99 at Time 1) participating in a longitudinal study in Belfast, Northern Ireland. Utilizing hierarchical linear modeling, the results show that the effect of exposure to sectarian antisocial behaviors has a stronger effect on youth emotion problems for older adolescents. The results also show that youth with higher strength of group identity reported fewer emotion problems in the face of sectarian antisocial behavior but that this buffering effect is stronger for Protestants compared to Catholics. Implications are discussed for understanding the role of social identity in postaccord societies.